Legal Protection for Foreign Trademark Holders in Indonesia (Supreme Court Decision No. 281 K/Pdt.Sus-HKI/2020) - Fokky Fuad; Fauzan Rayendra, Fadhil (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This article discusses the legal protection of foreign trademarks in Indonesia, with a focus on a case decided by the Supreme Court in Decision Number 281 K/Pdt.Sus-HKI/2020. In the era of global trade, trademarks have become one of the key elements in maintaining commercial competitiveness. Indonesia has implemented legal protection as stipulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This article analyzes how the rights of foreign trademarks can be protected and the legal considerations used by judges in trademark dispute cases. One of the main highlights is the process of registering foreign trademarks and the challenges faced in protecting well-known trademarks in Indonesia. This study adopts a normative juridical approach and case study to evaluate the Supreme Court's decision related to famous foreign trademarks, particularly in the dispute between Diesel S.p.A and another party in Indonesia. The research findings indicate that although legal protection is available, the implementation and enforcement of foreign trademark protection still face various challenges.